Analisis Efektivitas Pengikat Fosfat Tablet Kalsium Karbonat yang Dikunyah Dibandingkan yang Ditelan Utuh pada Pasien Penyakit Ginjal Kronis Dengan atau Tanpa Gangguan Saluran Cerna - Prawesti, Galuh Nawang; Yogiantoro, R. Moh.; Widodo, Gunawan; Purnamayanti, Anita (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2019)
Chronic Kidney Disease (CKD) patient with Mineral and Bone Disorder complication have to chew calcium carbonate tablet as a phosphate binder, but infact, patient swallow it in a whole. Gastrointestinal (GI) disorders can affect the efficacy of medicine. This study aims to analyze the effectiveness comparation of chewed and whole swallowed calcium carbonate tablet in CKD patients with or without gastrointestinal disorders. This prospective quasi experimental study with non-inferiority design was conducted on May 28th to August 22nd 2012, with 22 sample (stage 3-5 CKD), 14 men, 8 women, divided into 4 groups (1st: patients with GI disorder and whole swallowed calcium carbonate, 2nd: with GI disorders and chewed tablet, 3rd: without GI disorders and whole swallowed tablet, 4th group: without GI disorders and chewed tablet, all tablet are used with meal). Before and after the 6th week research period, calcium and phosphate blood levels measurements had been taken, adherence had been measured every two weeks using the Morisky questionnaire and pill count. The results showed that there was no significant difference in the increased of calcium levels, except for group 1 compared to group 3 (p = 0.027), the decreased phosphate levels (p = 0.724; 0.089; 0.089; 0.414; 0.569; 1.000) and the value of the product calcium-phosphate (p = 1.000; 0.308; 0.186; 0.414; 0.425; 0.728). The conclusion is that the way to use the medicine and the states of gastrointestinal disorders did not significantly influence the effectiveness of calcium carbonate tablet.